2017
DOI: 10.5380/biofix.v3i1.55831
|View full text |Cite
|
Sign up to set email alerts
|

Digestão Anaeróbia De Resíduos Alimentares Utilizando Ensaios BMP

Abstract: A preocupação com a preservação do meio ambiente e a necessidade de diversificação da matriz energética são alguns dos fatores que têm impulsionado a busca por energias alternativas. Nesse contexto, o presente trabalho analisou o processo de digestão anaeróbia de resíduos alimentares provenientes de um restaurante popular, observando o potencial bioquímico da geração de metano. O experimento consistiu no uso de reatores anaeróbios em regime batelada com volume de 250 mL, sendo 150 mL de volume útil à geração d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…The results were promising when compared to the study conducted by Leite et al (2014) that when using typically vegetable waste, in addition to sewage sludge, a removal of 51% of COD was obtained. In contrast, Gueri et al (2018) obtained a reduction of 80.98 -81.63%, using food waste and anaerobic sludge in bench reactors. Talha et al (2016) working with sugarcane bagasse, obtained a COD removal of 69.64%.…”
Section: Organic Removalsmentioning
confidence: 86%
“…The results were promising when compared to the study conducted by Leite et al (2014) that when using typically vegetable waste, in addition to sewage sludge, a removal of 51% of COD was obtained. In contrast, Gueri et al (2018) obtained a reduction of 80.98 -81.63%, using food waste and anaerobic sludge in bench reactors. Talha et al (2016) working with sugarcane bagasse, obtained a COD removal of 69.64%.…”
Section: Organic Removalsmentioning
confidence: 86%
“…Consistent with Gueri et al (2018), food residues have a good potential to produce biogas since they present values above the average of most substrates when evaluating specific methane production. The estimation of this generation can be done through experimental studies carried out in bench reactors such as the biochemical methane potential (BMP) test.…”
Section: Introductionmentioning
confidence: 77%
“…The anaerobic biodigesters was monitored by means of the biochemical methane potential (BMP) tests, which measure the biodegradability of organic matter through total methane production (Gueri, 2018). Nine lab bench biodigesters were used ( Figure 1).…”
Section: Laboratory Tests To Obtain Biogasmentioning
confidence: 99%
“…The internal pressure of the flasks was converted into volume of the generated biogas by Equations 1 and 2, for the different sweet potato genotypes evaluated and transformed to the normal conditions of temperature and pressure (CNTP) (Harries et al, 2001). This procedure was performed by Alves (2008), Gueri (2018), recommended by Angelidaki et al (2009) and reported by Alzate et al (2012). (1) Where: T = time (days); PF (mbar) = bottle pressure in millibar; VUF (L) = useful volume of the bottle in liters; TF (K) = bottle temperature in Kelvin.…”
Section: Test Monitoring Bmpmentioning
confidence: 99%